2014
DOI: 10.3791/51236
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Oral Fatty Acid Thresholds, Fat Perception, Fatty Food Liking, and Papillae Density in Humans

Abstract: Emerging evidence from a number of laboratories indicates that humans have the ability to identify fatty acids in the oral cavity, presumably via fatty acid receptors housed on taste cells. Previous research has shown that an individual's oral sensitivity to fatty acid, specifically oleic acid (C18:1) is associated with body mass index (BMI), dietary fat consumption, and the ability to identify fat in foods. We have developed a reliable and reproducible method to assess oral chemoreception of fatty acids, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(76 citation statements)
references
References 36 publications
2
70
0
2
Order By: Relevance
“…Recent studies have shown that GPR120 dysfunction leads to obesity, glucose intolerance, and fatty liver (Ichimura et al 2012;Janssen and Depoortere 2013;DiPatrizio 2014). Moreover, several studies reported a difference in the OA detection threshold among human individuals and an inverse correlation between body mass index (BMI), a measure of body fat, and oral OA sensitivity (Stewart et al 2010(Stewart et al , 2011Haryono et al 2014). BMI is defined as the weight in kilograms divided by the square of the height in meters (kg/m 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that GPR120 dysfunction leads to obesity, glucose intolerance, and fatty liver (Ichimura et al 2012;Janssen and Depoortere 2013;DiPatrizio 2014). Moreover, several studies reported a difference in the OA detection threshold among human individuals and an inverse correlation between body mass index (BMI), a measure of body fat, and oral OA sensitivity (Stewart et al 2010(Stewart et al , 2011Haryono et al 2014). BMI is defined as the weight in kilograms divided by the square of the height in meters (kg/m 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…OA is a fatty acid that is commonly found in the food supply and is easy to use because it is liquid at room temperature, even though it is poorly soluble in water (Haryono et al 2014). Thus, the OA solution used in the present study consisted of an emulsion of food grade OA (Sigma-Aldrich, St. Louis, MO, USA) in non-fat milk (Morinaga Milk Industry, Tokyo, Japan) and was newly prepared for every session, following a previously established method (Stewart et al 2010;Kulkarni and Mattes 2013;Haryono et al 2014;Asano et al 2016).…”
Section: Determination Of the Increase In The Sfr Induced By Oamentioning
confidence: 99%
“…Thus, the OA solution used in the present study consisted of an emulsion of food grade OA (Sigma-Aldrich, St. Louis, MO, USA) in non-fat milk (Morinaga Milk Industry, Tokyo, Japan) and was newly prepared for every session, following a previously established method (Stewart et al 2010;Kulkarni and Mattes 2013;Haryono et al 2014;Asano et al 2016). OA was stored at -20°C before use.…”
Section: Determination Of the Increase In The Sfr Induced By Oamentioning
confidence: 99%
See 2 more Smart Citations